Alzheimer Disease: Postmortem Neuropathologic Correlates of Antemortem (1)H MR Spectroscopy Metabolite Measurements(1) - Kantarci, Kejal (Radiological Society of North America, 2008)
Purpose: To determine the neuropathologic correlates of antemortem hydrogen 1 ((1)H) magnetic resonance (MR) spectroscopy metabolite measurements in subjects with Alzheimer disease (AD)-type pathology. Materials and Methods: This study was approved by the institutional review board and was compliant with HIPAA regulations. Informed consent was obtained from each subject. The authors identified 54 subjects who underwent antemortem (1)H MR spectroscopy and were clinically healthy or had AD-type pathology with low to high likelihood of AD according to National Institute on Aging–Reagan neuropathologic criteria at autopsy. They investigated the associations between (1)H MR spectroscopy metabolite measurements and Braak neurofibrillary tangle stage (Braak stage), neuritic plaque score, and AD likelihood, with adjustments for subject age, subject sex, and time between (1)H MR spectroscopy and death. Results: Decreases in N-acetylaspartate–to-creatine ratio, an index of neuronal integrity, and increases in myo-inositol–to-creatine ratio were associated with higher Braak stage, higher neuritic plaque score, and greater likelihood of AD. The N-acetylaspartate–to–myo-inositol ratio proved to be the strongest predictor of the pathologic likelihood of AD. The strongest association observed was that between N-acetylaspartate–to–myo-inositol ratio and Braak stage (R(N)(2) = 0.47, P < .001). Conclusion: Antemortem (1)H MR spectroscopy metabolite changes correlated with AD-type pathology seen at autopsy. The study findings validated (1)H MR spectroscopy metabolite measurements against the neuropathologic criteria for AD, and when combined with prior longitudinal (1)H MR spectroscopy findings, indicate that these measurements could be used as biomarkers for disease progression in clinical trials. © RSNA, 2008